INNV-02. ARE WE AGGRESSIVE WITH OUR GLIOBLASTOMA PATIENTS: A PROPOSED TOOL TO EVALUATE CENTERS ATTITUDES IN TREATMENT OF GLIOBLASTOMA. (11th November 2019) - Al Abdulsalam, Hissah; Alhothali, Wajda; Alkhalidi, Hisham; Orz, Yasser; Alobaid, Abdullah; Bafaqeeh, Mohammed; Shaffi Ahamed, Shaik; Hussain, Sajjad; Albader, Fahad; AlSaeed, Eyad; Ibrahim, Ahmed; Abdel Warith, Ahmed; et al.
Abstract: INTRODUCTION: Glioblastoma is the most common malignant primary brain tumor in adults. Optimal treatment for glioblastoma requires a multidisciplinary approach and knowledge of complications from both the disease and its treatment. Despite modern advances in the standards of care, the outcome in patients with Glioblastoma remains poor. Thus, it is crucial to optimize treatment strategies to improve over-all survival in patients with Glioblastoma, with the therapeutic challenge of "how aggressive a physician should be?" OBJECTIVES: We herein propose a novel method to compare aggressiveness in the standard of care between multiple centers, using a novel tool, and provide a more precise cut-off definition of aggressiveness. METHOD: Multiple centers were included. A novel case-based questionnaire was generated which included only certain parameters, and then sent and answered jointly by tumor board members from each center. We then stratified centers into more aggressive vs. less aggressive based on our proposed Aggressiveness (AS) score. RESULTS: In our novel cases, center A scored an AS score of 44 (Mean ± SD; 3.67 ± 1.07), while center B scored 49 (Mean ± SD; 4.08 ± 0.90) In real cases, center A scored 40 (Mean ± SD; 3.25 ± 1.42), while center B scored 44 (Mean ± SD; 3.75 ± 1.29). Our results showed consistency between centers evaluated using our tool. Age and presence of comorbidities were the most influential parameters. CONCLUSION: In the current study, we present a novel and a reliable tool that can be easily used and replicated to compare aggressiveness in the treatment of Glioblastoma between multiple centers. The methodology we used has never been previously proposed and can serve as a novel concept to compare aggressiveness in treatment of all incurable diseases that require a multidisciplinary approach.